Study on the relationship between medical staff’s knowledge, attitudes, and practices regarding medical waste classification and personality traits - Wang, Jinyan; Liu, Meifeng; Wang, Deyu (Frontiers in Health Services, 2025)
Aim and objectivesThis study aims to assess healthcare workers’ medical waste management knowledge, attitudes, and practices (KAP) and the influencing Factors; The study objectives are to explore the association between medical staff's personality traits and their KAP toward medical waste classification.MethodsA self-designed questionnaire assessing medical staff's knowledge, attitudes, and Practices toward medical waste classification, along with the Ten-Item Personality Inventory - Chinese version (TIPI-C), was administered to 420 nurses and doctors at a hospital in China. Group comparisons were performed using t-tests and ANOVA. Correlations between medical staff's knowledge and attitudes toward medical waste classification and TIPI-C were analyzed using Spearman's correlation. Influencing factors were examined through multiple stepwise regression analysis.ResultsThis study assessed the knowledge, attitudes, and practices (KAP) of medical waste classification among 420 healthcare professionals (214 nurses, 206 doctors) in a large Chinese hospital. The overall scores were 8.70 ± 1.63 for knowledge, 18.54 ± 3.11 for attitudes, and 24.20 ± 4.94 for practices. Nurses demonstrated significantly higher KAP levels than doctors across all domains (P < 0.05). Female staff outperformed males in knowledge (β = −0.162, p = 0.002), attitudes (β = −0.266, P < 0.001), and practices (β = −0.212, P = 0.002). Longer working experience was positively associated with knowledge (β = 0.113, P = 0.019). Higher education was also a positive predictor of knowledge (β = 0.132, P = 0.007). Among personality traits, openness showed a significant positive correlation with attitudes (r = 0.187, P < 0.01) and was a predictor of both attitudes (β = 0.160, P = 0.017) and practices (β = 0.154, P = 0.025) in regression analysis.ConclusionsThis study revealed moderate to high levels of knowledge, attitudes, and practices (KAP) regarding medical waste classification among healthcare professionals, with nurses and female staff demonstrating significantly higher KAP scores. Key influencing factors identified include occupation, gender, years of experience, education level, and the personality trait of openness. These findings highlight the need for targeted, role-specific training programs to enhance compliance and safety in medical waste management. In addition to training, policy implications should include the integration of medical waste management into regular performance assessments and accountability mechanisms. Furthermore, fostering a culture of openness and continuous improvement through institutional support and feedback systems is recommended to sustain positive behavioral change.